THU0366 Gastrointestinal infections in patients with spondyloarthritis treated with anti-tnf drugs: results of gisea register. (15th June 2017) - Atzeni, F; Panetta, V; Sebastiani, M; Salaffi, F; Carletto, A; Foti, R; Iannone, F; Elisa, G; Govoni, M; Marchesoni, A; Favalli, EG; Gorla, R; et al.
Abstract : Background: Tumour necrosis factor (TNF) plays a pivotal role in controlling intracellular of bacterial infection. The BSR Biologics Register (BSRBR) has reported an increase in the occurrence of listeria and salmonella infections in anti-TNF-treated rheumatoid arthritis patients in comparison with those patients treated with non-biological DMARDs. Objectives: The aim of this study was to determine the incidence of gastrointestinal infection in the anti-TNF-treated spondyloarthritis (SpA) patients in the GISEA registry, and identify the factors associated with its development. Methods: The prospective GISEA registry was designed to collect real-world clinical data concerning patients with RA or SpA treated with biological drugs. The baseline information includes demographics, disease duration, HAQ-DI, DAS-28, BASDAI, BASFI and BASMI scores, steroid use, smoking history and comorbidities. Results: Of the 3321 anti-TNF-treated SpA patients in the registry (1731 males, 52.2%; mean age 47±13 years; median disease duration three years, interquartile range [IQR] 0–8), 1065 (32%) were treated with infliximab (IFN), 1052 (32%) with adalimumab (ADA), and 1204 (36%) with etanercept (ETN). Two thousand, one hundred and five patients (63.4%) had a median of one comorbidity (IQR 0–2], the most frequent being hypertension (701), thyroid diseases (281), diabetes mellitus (207), cardiopathy (189), and osteoporosis (145). In combination with the biological drug, 919 patients (27.7%) received steroids and 2451 (79.9%) at least one DMARD. The median follow-up was three months (IQR 1–2 years). Twenty-two patients 0.7% experienced bacterial gastrointestinal infections, the most frequent being due to listeria, klebsilla and salmonella. The crude incidence rate was 2.5 per 1000 patient-years (95% CI 1.6–3.7). Univariate analysis showed that female gender (OR 3.9, 95% CI 1.5–10.0; p=0.004) and comorbidities (OR 3.4, 95% CI 1.0–3.5; p=0.049) were associated with a high risk of gastrointestinal infections, and that the use of IFN rather than ETN and ADA (p=0.712 and p=0.238) was not associated with a higher risk of gastrointestinal infections. Furthermore, univariate models showed that age (p=0.738), disease duration p=0.090, previous DMARDs (p=0.616), and HAQ (p=0.674) and BASFI (scores p=0.850) were not statistically significant predictors of gastrointestinal infections. Conclusions: The incidence rate of gastrointestinal infections in SpA patients treated with anti-TNF drugs is not increased. Being female and having comorbidities are predictive factors of gastrointestinal infections. Disclosure of Interest: None declared